SKOLLIES IN MY SKOOL - MENINGS WAT SAAK MAAK/SKOLLIES IN MY SCHOOL – OPINIONS THAT MATTER - Dykes, Glynnis; Brey, Fairoza; Carelse, Shermaaz; Davids, Ronel; Human-Hendricks, Anja; Lukelelo, Nomvuyo (Social Work/Maatskaplike Werk, 2021)
There is considerable concern about the increasing phenomenon of school gangs on the Cape Flats. This article emanated from a larger research study undertaken over a three-year period (2016-2018) by Social Work students from the University of the Western Cape. The objective was to explore and describe the experiences of school learners about youth in gangs, and to develop appropriate interventions. This article presents the findings of the 2016 study. A qualitative approach, utilising an exploratory and descriptive design, was used. Individual interviews were conducted with 400 learners from eight schools on the Cape Flats using purposive and convenient sampling. Six main themes are presented that emerged from thematic data analysis. These include poverty and unemployment, unsafe spaces in townships, substance abuse, the power of gangs, peer pressure and bullies as well as family relationships and family dynamics. Ethics approval to conduct the study was obtained from the research ethics committee of the University.